Leadership preparation in China: providers’ perspectives - Xue, Shan; Bush, Tony; Ng, Ashley Yoon Mooi (Dokuz Eylul University, 2020)
In China, accreditation training programme has been a compulsory programme for all the aspiring and new principals, which is also a part of National Training Plan. Under such hierarchical system, leadership preparation in China is supported, implemented, evaluated, and also, constrained by different levels of administrative organisations and various professional providers. The purpose of the study was to understand the role definition and task allocation of different levels of administrations and providers, as well as how they work as a whole for leadership preparation. The study features a qualitative design that combined data from policy document analysis and semi-structured interviews of people who directly involved in this procedure. Data collected in qualitative strand were coded and analysed thematically through discourse analysis. We identified a completed, but disintegrated system for leadership preparation. The results provided important practice and policy implications. We suggest the collaboration and appropriate supervision among different providers and develop a systematic mechanism for principal preparation and development.